Antibacterial Activity Test of Methanol Extract of Gracilaria sp. against Escherichia coli Using Disc Diffusion Method: Uji Aktivitas Antibakteri Ekstrak Metanol Gracilaria sp. terhadap Escherichia coli Dengan Metode Difusi Cakram - Ammanda Sadiva Ajeng Pawesti; Kusuma Handayani; Endah Setyaningrum; Hendri Busman (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2025)
The utilization of marine resources as an alternative source of natural antibacterial agents has been increasingly developed in recent years. Gracilaria sp., a type of red algae, is known to contain biologically active compounds with potential antibacterial properties, particularly against Escherichia coli. This study aims to determine the antibacterial potential of methanol extract from Gracilaria sp. against E. coli using an experimental method with a Completely Randomized Design (CRD). Data were analyzed using One-Way ANOVA followed by Tukey's test. The stock solution of the extract was prepared at a concentration of 100 mg/mL and tested at concentrations of 0.05%, 1%, 5%, and 10%, with ciprofloxacin as the positive control and sterile distilled water as the negative control. The experiment was conducted with three replications. The results showed that the methanol extract of Gracilaria sp. formed inhibition zones at the highest concentrations of 10% and 5%, with an average diameter of only 0.075 mm. Thus, the methanol extract of Gracilaria sp. exhibits weak antibacterial potential against Escherichia coli, as the inhibition zone formed was significantly smaller than that of the positive control, which reached 1.7 mm.